Pleuridium tucumanensis sp. Nov. (section Pleuridium: Ditrichaceae) from Argentina - Colotti, Maria Teresita de Jesus (2019)
We present the description and illustration of Pleuridium tucumanensis, a new species of Pleuridium, section Pleuridium, from Argentina. P. tucumanensis have spreading incurved leaves, a rare characteristic in the genus. It is compared with related species highlighting their morphological differences.